(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2020)
After more than 100 years of presence in Latin American universities, the concepts and ideas that have built significance for university extension, and their respective practices, have been diverse.They gave rise to different orientations not always compatible with each other. One one sido, cuarenta based on assistance and philanthropy, on the other, approaches based on the ideal of social and political emancipation. The long night of the military dictatorships and the neoliberal policies in the 1990s substantially modified the context in the region. It was there when a new trend emerged within the university extension, one that proposed a critical reading of the traditions and political-ideological matrices of extension based on the new context. We refer to the current of the Latin American and Caribbean Critical Extension (ECL and C), born in response to the new hegemonic formats of technology transfer that established a commodified link with the environment, threatening the very existence of university social commitment. In this article we propose to address the traditions, theoretical, methodological and pedagogical matrices that converge in the emergence ofcriticalextension and nurture its praxis.